Semantic broadening in the translation of Arabic religious terms: Evidence from al-raḥīq al-makhtūm - Ditania Rakhma Andini; Arief Ma'nawi (Diwan: Jurnal Bahasa dan Sastra Arab, 2026)
Al-Raḥīq al-Makhtūm is a globally recognized and authoritative biography of the Prophet Muhammad. Translating its religious terms requires precise translation to avoid conceptual misunderstandings. While previous studies have extensively examined religious translation strategies, ideologies, and equivalence, research explicitly investigating micro-level mechanisms of semantic broadening through semantic decomposition remains scarce. This article examines the phenomenon of semantic broadening in the translation of Arabic religious terms in al-Raḥīq al-Makhtūm and its Indonesian translated version, Sirah Nabawiyyah. The study aims to identify the forms of semantic broadening and to examine the factors underlying this phenomenon. It employs a descriptive qualitative method incorporating a comparative approach. The data are analyzed using semantic decomposition to compare terms between the source and target texts. Findings indicate that semantic broadening occurs consistently through the omission of diagnostic semantic features in the source language. Of the ten categories identified, five are examined in depth: eschatological terms, specialized religious activities, religious figures, religious morals and ethics, and revelatory terms. Four main factors underlie this phenomenon: the demand for natural collocational patterns in the target language, the translator’s communicative strategies through generalization and modulation techniques, lexical gaps, and differences in cultural and religious contexts. The findings confirm that semantic broadening is not a translation error, but rather a natural consequence of cross-cultural translation aimed at maintaining textual acceptability and readability. Theoretically, this study demonstrates that semantic decomposition effectively traces meaning shifts in religious texts. Practically, it guides translators of Islamic history to prioritize general equivalents for readability over rigid literalism.